Exercise Pre Operatif pada Pasien Kanker Payudara dengan Mastektomi - Nurmalasari Nurmalasari; Allenidekania Allenidekania (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the effect of preoperative exercise on breast cancer patients with mastectomy. The research design is a systematic review using the PubMed, ScienceDirect, and Scopus databases. The research results obtained 199 articles and nine articles were relevant and met the requirements. The preoperative exercise showed a positive effect on the side effects of mastectomy. In conclusion, preoperative exercise intervention can reduce complaints or side effects felt by breast cancer patients after undergoing a mastectomy, including pain, limited range of motion of the shoulder joint, decreased shoulder function, lymphedema, and quality of life. Keywords: Preoperative Exercise, Breast Cancer, Mastectomy